Cenozoic sill intrusion in the central and southern East China Sea Shelf Basin. (September 2020) - Yao, Zewei; Li, Chun-Feng; He, Guangyu; Tao, Tiansheng; Zheng, Xiaoli; Zhang, Tao; Tang, Xianjun; Zhao, Tianliang
Abstract: Cenozoic igneous rocks dominated by basalts are exposed sporadically onshore East China, and they provide important information about the Cenozoic evolution of the region. Importantly, their geometries and distribution are still not well constrained in the 200–600 km wide offshore continental shelf region. Based on seismic profiles, this study presents the geometric characteristics of 133 igneous sills that are widely distributed in the central and southern regions of the East China Sea Shelf Basin (ECSSB). Sills in high-amplitude, continuous seismic reflections mostly occur in a time interval of 1.1–3.3 s in multiple seismic profiles, corresponding to a depth range of 1.1–4.8 km. They can be classified into five types: saucer-shaped sills, strata-concordant sills, laccoliths, inclined sheets, and hybrid sills. Of these, the saucer-shaped sills predominate. Strata deformation associated with these igneous sills indicate that sill intrusion has become intense since the Miocene, and it potentially affected petroleum systems in the ECSSB. Forced folds induced by the sills are prospective petroleum traps. We infer that sill intrusion in the ECSSB was due to magma upwelling caused by dehydration and/or small-scale convection in a large mantle wedge above the stagnant Pacific slab. The subduction of the Philippine Sea plate resulted in tectonic inversion in the ECSSB and extension in the Okinawa Trough since the Early Miocene triggered more magmatism in the tectonically thinned ECSSB. Thick sedimentary strata over a thin crust in the ECSSB may have induced more intrusive than extrusive Cenozoic magmatism. Highlights: Sill geometry and distribution in the central and southern ECSSB are presented for the first time. Igneous sills are common in the ECSSB and can be classified into five geometric types. Sill intrusion in the ECSSB became intense since the Miocene.